Transfer learning and explainable AI with Python. (Manning Publications, 2021)
Anuradha will walk you through her Liveproject series named : "Transfer Learning for Dicom Image Classification" in which you can explore two important topics in current deep learning research-firstly the concept of transfer learning and secondly explainability in deep learning and artificial intelligence. During the session, she will show the implementations of conventional deep learning models and of those using transfer learning. Then you will see an example of explainable AI as part of this liveProject series. Coding samples on these topics will be demonstrated and explained. Anuradha will also talk about some good literature resources by Manning publications on the above two topics.